2022
DOI: 10.1044/2021_jslhr-21-00406
|View full text |Cite
|
Sign up to set email alerts
|

Memory-Paced Tapping to Auditory Rhythms: Effects of Rate, Speech, and Motor Engagement

Abstract: Purpose: Humans have a near-automatic tendency to entrain their motor actions to rhythms in the environment. Entrainment has been hypothesized to play an important role in processing naturalistic stimuli, such as speech and music, which have intrinsically rhythmic properties. Here, we studied two facets of entraining one's rhythmic motor actions to an external stimulus: (a) synchronized finger tapping to auditory rhythmic stimuli and (b) memory-paced reproduction of a previously heard rhythm. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…Second, the coupling of neuronal oscillations to an external beat frequency, observed in passive listening to rhythm, is enhanced when gestures, like finger tapping, are simultaneously produced [70]. Also, a more accurate and less variable reproduction of an isochronous sequence is observed after tapping along with the pattern, compared to passively listening before tapping [71]. Altogether, these observations support the idea that people build an internal representation of the beat by detecting the periodicity in sensory inputs without actual movement, but that this internal representation is nevertheless consolidated with engaging the motor system.…”
Section: Influence Of Motor Engagement and Sensorimotor Learningmentioning
confidence: 99%
“…Second, the coupling of neuronal oscillations to an external beat frequency, observed in passive listening to rhythm, is enhanced when gestures, like finger tapping, are simultaneously produced [70]. Also, a more accurate and less variable reproduction of an isochronous sequence is observed after tapping along with the pattern, compared to passively listening before tapping [71]. Altogether, these observations support the idea that people build an internal representation of the beat by detecting the periodicity in sensory inputs without actual movement, but that this internal representation is nevertheless consolidated with engaging the motor system.…”
Section: Influence Of Motor Engagement and Sensorimotor Learningmentioning
confidence: 99%
“…Auditory-motor interaction in speech processing has been an active field for decades (Hickok et al, 2011;Poeppel and Assaneo, 2020). Emerging evidence from finger-tapping studies suggests that this interaction exists not only at the basic rhythmic level (Rathcke et al, 2021;Kliger Amrani and Zion Golumbic, 2022) but also at higher levels, subject to variations in both acoustic and syntactical 10. 3389/fnins.2023.1146298 structures (Falk and Dalla Bella, 2016;Falk et al, 2017;Hilton and Goldwater, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence has demonstrated that auditory-motor synchronization not only reflects basic beat-level perception and action timing (Cannon and Patel, 2021) but also drives more complex forms of rhythm perception, including those involving hierarchical rhythms (Iversen and Balasubramaniam, 2016). Recently, interest has grown in using speech stimuli (Lidji et al, 2011;Falk and Dalla Bella, 2016;Falk et al, 2017;Rathcke et al, 2021;Kliger Amrani and Zion Golumbic, 2022;Wei et al, 2022). Similar to the findings with non-speech stimuli, participants can accurately translate perceived rhythms in the speech into finger-tapping movements.…”
Section: Introductionmentioning
confidence: 90%
“…A key feature of the SMA is that it is involved in both motor and non-motor tasks and, in particular, seems to create a bridge between the two networks. As such, the integration of sensorimotor systems with a forward prediction model allows for a stabilization of the internal timing interval, which is essential for beat perception in music (Amrani and Golumbic, 2022; Rosso et al, 2023).…”
Section: Introductionmentioning
confidence: 99%